City - Phil Hubbard (Routledge, 2006)
City provides an accessible yet critical introduction to one of the key concepts in human geography. Always at the heart of discussions in social theory, the definition and specification of ‘the city’ nonetheless remains illusive. In this volume, Phil Hubbard locates the concept of ‘the city’ within current traditions of social thought, providing a basis for understanding its varying usages and meanings through a critical discussion of the contribution of key authors and thinkers.